A Study of Association of Psoriasis and Type 2 Diabetes Mellitus: A Comprehensive Systematic Review - Marvelo Surya Rahman Djohar; Bambang Ratio Setiyarso (Publikasi Indonesia, 2024)
Diabetes mellitus is a significant risk factor in psoriasis, a chronic inflammatory disease with a high genetic predisposition. The association between psoriasis and diabetes mellitus is inconsistent, with some studies finding a higher risk of metabolic disorders in psoriasis patients. However, meta-analytical studies confirm a significant association between adult psoriasis and obesity, hypertension, diabetes, dyslipidemia, and metabolic syndrome. Understanding this association can help develop treatments and plans to alleviate the burden of these conditions. This systematic review focused on full-text English literature published between 2014 and 2024, adhering to PRISMA 2020 principles. Without a DOI, editorials and review papers that were published in the same journal as the submission were not accepted. ScienceDirect, PubMed, and SagePub were among the many web resources used to compile the literature. Using reliable resources, including Science Direct, SagePub, and PubMed, the study examined over 7,000 publications. Following the determination that eight publications warranted further inquiry, a more thorough examination of the full corpus was conducted. Diabetes mellitus risk in psoriasis patients is significantly increased due to insulin resistance, a common pathogenic mechanism in both psoriasis and metabolic syndrome. Treatment can reduce this risk by reducing proinflammatory cytokines and increasing anti-inflammatory cytokine.